نظرية تقوية الحديث بالشواهد والمتابعات عند المحدّثين - Hasin, H.; Jamilin, A. K.; Ramle, M. R. (Universiti Sains Islam Malaysia, 2024)
Discussion on the issue of escalating the status of weak (dha’if) hadith through the process of al-syawahid and al-mutaba’at to the status of good (hasan) hadith is strongly disputed by the modern hadith scholars. The process is known as al-I’tibar. Through the process, the status of narrations such as authentic (sahih) and others can be known by analysing each related narrations and cross referring the narrations to determine its consistency (ittifaq), contradiction (ikhtilaf) or singleness (tafarrud) which also as indicator the strength of memory of a narrator. Consequently the criticism or praiseworthiness of the narrators can be established afterward. Thus this paper aim to focus on the issue of escalating status of hadith by using the process of al-I’tibar and its relation with good hadith upon which it is discover the narration pose certain weakness by some of hadith scholars. The research is crucial since it is related deeply with the main principle and discourse in the science of hadith which is escalating the status of weak hadith which play vital role in determining the validity of the hadith.